2006
DOI: 10.1073/pnas.0510599103
|View full text |Cite
|
Sign up to set email alerts
|

Association of brefeldin A-inhibited guanine nucleotide-exchange protein 2 (BIG2) with recycling endosomes during transferrin uptake

Abstract: ADP-ribosylation factors (ARFs) are critical in vesicular trafficking. Brefeldin A-inhibited guanine nucleotide-exchange protein (BIG)1 and BIG2 activate ARFs by accelerating replacement of bound GDP with GTP. Additional and differing functions of these Ϸ200-kDa proteins are now being recognized, as are their independent intracellular movements. Here, we describe the localization in COS7 cells by immunofluorescence microscopy of BIG2, but not BIG1, with structures that have characteristics of recycling endosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 40 publications
2
56
0
1
Order By: Relevance
“…Depletion of BIG1 or BIG2 using specific siRNAs or overexpression of a dominant-negative GEF-inactive Sec7 domain mutant interfered with vesicular transport of specific proteins from TGN or recycling endosomes to the plasma membrane (24,27,28,41). Interference with β-catenin trafficking by expression of GEF-inactive BIG1 or BIG2, but not wild type (WT) or BIG1 AKAP mutant, led to its accumulation in perinuclear clusters (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Depletion of BIG1 or BIG2 using specific siRNAs or overexpression of a dominant-negative GEF-inactive Sec7 domain mutant interfered with vesicular transport of specific proteins from TGN or recycling endosomes to the plasma membrane (24,27,28,41). Interference with β-catenin trafficking by expression of GEF-inactive BIG1 or BIG2, but not wild type (WT) or BIG1 AKAP mutant, led to its accumulation in perinuclear clusters (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Microscopically, BIG1 was seen mainly at the trans-Golgi network (TGN), sometimes partially overlapping BIG2, which was associated also with recycling endosomes (24-26), e.g., in moving proteins and lipids among TGN, endosomes, and cell surface (24,(27)(28)(29). Although actions of BIG1 and BIG2 at the TGN were described as "redundant" (27), each protein clearly has specific roles in moving proteins and lipids that are not shared with the other (24,30,31). Overexpression in cultured cells of mutant BIG2 lacking Arf GEF activity markedly altered intracellular distributions of E-cadherin and β-catenin (32).…”
mentioning
confidence: 99%
“…The ARF-GEF family is divided into several subfamilies; these include the brefeldin A (BFA)-sensitive GBF/BIG subfamily, whose members localize to and function at the Golgi apparatus, and can activate class I and class II ARFs (Jackson and Casanova, 2000;). We and others have shown that BIG2 activates class I ARFs (ARF1 and ARF3), localizes to recycling endosomes as well as the TGN, and is required for the integrity of recycling endosomes (Ishizaki et al, 2008;Shen et al, 2006;. However, it has not yet been clarified whether ARF1 and ARF3 participate in endosome integrity downstream of BIG2, in part because it is not yet known whether these ARFs are associated with endosomal compartments.…”
Section: Introductionmentioning
confidence: 99%
“…From the Sec7/BIG group BIG1 and BIG2 proteins were purified from bovine brain together with macromolecular complexes (>670 kDa) (Morinaga et al 1996). Several studies reported the association of BIG proteins with the trans-Golgi network (TGN) (Mansour et al 1999;Yamaji et al 2000;Shinotsuka et al 2002a,b;Zhao et al 2002), in addition, the association with recycling endosomes was also demonstrated Shen et al 2006). BIG1 and BIG2 proteins revealed considerable similarities to each other in the sequence and domain organization (Mouratou et al 2005), however, it is still not clear whether both proteins play redundant or distinct role in the control of membrane trafficking.…”
Section: Introductionmentioning
confidence: 99%